Use Of CCTV To Improve AMC Unit Supervision Management At Kualanamu International Airport - Muhammad Caesar Akbar; Inda Tri Pasa; Dinda Suci Aliya Permata (Journal of Information Technology, computer science and Electrical Engineering, 2024)
CCTV is essential for maintaining security and increasing operational efficiency. This research helps evaluate the use of CCTV in improving monitoring management of the Apron Movement Control (AMC) unit on the air side of Kualanamu International Airport. AMC is responsible for managing the movement of aircraft, vehicles and personnel on the apron. With the increasing complexity and volume of air traffic, adequate surveillance systems have become increasingly important. The method used in this research is descriptive qualitative. The research results show that the use of CCTV provides various benefits, especially for AMC officers on the air side of Kualanamu International Airport. Utilization of CCTV can increase security, operational efficiency and safety.